Current challenges facing ecotourism development in Iran - Sarasadat Makian; Farid Hanifezadeh (Journal of Tourismology)
Iran is a rich country in terms of natural, historical, and cultural resources appropriate for ecotourism development. Despite its many valuable attractions and growth potential, Iranian ecotourism has faced various problems that have slowed or even prevented its expansion. Thus, in order to plan to address these challenges, we need to identify them. This study highlights the challenges of Iranian ecotourism and identifies areas where further research is required by reviewing some of the previous studies on Iran’s ecotourism. Based on a literature review and thematic analysis, six different categories of challenges are presented: governance and planning, political, socio-economic, cultural; legal aspects; infrastructure; community awareness and knowledge; and environmental challenges. The study results indicated that the most significant challenges facing the Iranian ecotourism industry are governance, management, and planning issues. The research findings enhance our understanding of the current challenges of ecotourism in Iran that need to be rigorously investigated in the future and before any development planning projects. This study provides valuable insights for researchers, managers, and tourism officials on the development of Iranian ecotourism, which can be considered for future studies and planning.